Reactive Filters for Steel Melt Filtration1. Issue 1 (19th September 2012) - Aneziris, Christos G.; Dudczig, Steffen; Emmel, Marcus; Berek, Harry; Schmidt, Gert; Hubalkova, Jana
Abstract New carbon bonded Al2O3 filters with Magnesia–carbon (MgO–C) "reactive coatings" for high filtration efficiency of steel melts are studied with the aid of a special steel casting simulator in full controlled atmosphere. Due to the in situ reduction of MgO in the MgO–C coating and the formation of Mg vapor a reaction with the oxygen dissolved in the steel melt is triggered and leads to the formation of secondary MgO on the filter surface. With this approach not only primary and secondary inclusions can be effectively removed from the steel melt, but as well as less tertiary and quartenary inclusions can be expected due to less oxygen dissolved in the steel melt.